PERAN BIDAN DALAM PENCEGAHAN KEKERASAN TERHADAP ISTRI DI SLEMAN DAERAH ISTIMEWA YOGYAKARTA - , Nining Tunggal Sri Sunarti; , Dr. Ira Paramastri, M.Si., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Midwives are health worker who have an important and strategic position. Midwives provide sustain maternity care that and whole, focusing on aspects of prevention, promotion based on partnership and empowerment. Midwives had important role in the health care of women who are able to identify and help to overcome issue of violence against wives. Objective: To determine the role of midwives in the prevention of violence against wives in Sleman, Yogyakarta. Method: This research was a qualitative case study design and descriptive. Collecting data through focus group discussions and in-depth interviews. The research subjects were 36 people. The subjects in this study choised by purposive sampling. Analysis of data used an interactive model in the form reduction, presentation and conclusion/verification. Result and Discussion: The role of midwives in the prevention of violence against wives as educator, motivators, facilitators, advocators, and mediators. As educators, midwives provide education in the prevention of violence against wives to the community, provide direction to the volunteers. As motivators, midwives provide motivation to the community and volunteers to participate in activities aimed at the prevention of violence against wives. As facilitators, midwives facilitated activities in the community. As advocators, midwives help people to make choices in the prevention of violence against wives. As mediators, midwives are bridging communities to implement prevention of violence against wives. Conclusion: The role of health centers and village midwives in the prevention of violence against wives are as educators, empowerers, facilitators, advocates and mediators. But in practice independent midwife roles are relatively less common.